Effectiveness of Acceptance and Commitment Therapy on Psychological Flexibility, Emotional Self-Regulation, and Stress Coping Styles in Mothers of Children with Specific Learning Disorders - Shafiei, Zahra; Ghamari, Mohammad; Seadatee Shamir, Aboutaleb (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This research aimed to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) on psychological flexibility, emotional self-regulation, and stress coping styles in mothers of children with specific learning disorders.Materials and Methods: This quasi-experimental study employed a pre-test, post-test, and a three-month follow-up design. The study population included all mothers of children with specific learning disorders enrolled in the fifth grade of primary schools in District 17 of Tehran during the 2021-2022 academic year, from whom 40 participants meeting the inclusion criteria were selected through purposive sampling and randomly assigned into two groups of 20. Data collection was conducted using the Cognitive Flexibility Inventory (Dennis & Vander Wal, 2010), the Emotional Self-Regulation Questionnaire (Larsen & Prizmic-Larsen, 2004), and the Coping with Stressful Situations Questionnaire (Parker & Endler, 1994). Data analysis was performed using mixed ANOVA with SPSS version 25.Findings: Results indicated that Acceptance and Commitment Therapy is effective in improving scores of psychological flexibility, emotional self-regulation, and stress coping styles (P